2022
DOI: 10.3390/ma15134631
|View full text |Cite
|
Sign up to set email alerts
|

Laser Boronizing of Additively Manufactured 18Ni-300 Maraging Steel Part Surface

Abstract: The problem of insufficient wear resistance of maraging steels (MSt) has so far been solved mainly by the use of the thermochemical nitriding process, which has a number of limitations and disadvantages. In the present work, for MSt parts manufactured by laser powder bed fusion (LPBF), a more flexible laser alloying process was suggested as an alternative surface hardening process. The purpose of the present work is to give a better understanding on the possible hardening effect obtainable when amorphous boron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The formation of cracks is mentioned in work [21], where harder boride layers are obtained (up to ~1600 HV), but this issue was not considered more closely. In the previous work of the authors [25], the application of laser boronizing technology to modify the surface of additively manufactured MSt parts was demonstrated; single passes were formed in a wide laser parameter range. It was found that the laser melting of a surface with preplaced amorphous boron paste results in the solidification of the boridecontaining layer, which has increased hardness (up to 1700 HK).…”
Section: Introductionmentioning
confidence: 99%
“…The formation of cracks is mentioned in work [21], where harder boride layers are obtained (up to ~1600 HV), but this issue was not considered more closely. In the previous work of the authors [25], the application of laser boronizing technology to modify the surface of additively manufactured MSt parts was demonstrated; single passes were formed in a wide laser parameter range. It was found that the laser melting of a surface with preplaced amorphous boron paste results in the solidification of the boridecontaining layer, which has increased hardness (up to 1700 HK).…”
Section: Introductionmentioning
confidence: 99%